Marketing Mix Untuk Chronic Care: Dari Episodic Service Ke Relationship-Based Strategy - Amy Shientiarizki; ⁠Baiq Yulia Handayani; Maulianur Rizki; Wachyu Sulistiadi (LPPM Universitas Respati Indonesia, 2026)
Introduction: The shift in disease patterns from acute to chronic conditions requires a transformation in healthcare systems, moving beyond a focus on episodic service toward a sustainable relationship-based strategy. This study aims to analyze the differences between these two approaches and examine the role of the marketing mix (7P) in chronic care services. Methods: This study employs a qualitative approach with a descriptive-analytical design through a literature review. Data were obtained from scientific literature, regulations, and relevant reports, and analyzed using descriptive, prescriptive, and argumentative methods. Results: The findings indicate that episodic service is limited and does not ensure continuity of care, whereas a relationship-based strategy enhances patient engagement, treatment adherence, and clinical outcomes. The implementation of the marketing mix has been shown to support the development of more integrated and patient-centered service designs. Conclusion: Therefore, the implementation of a relationship-based strategy supported by the marketing mix is essential for improving the effectiveness of chronic care services and fostering long-term relationships between patients and healthcare providers.